Relationship between walking levels and perceptions of the local neighbourhood environment. Issue 1 (7th December 2006) - Alton, D; Adab, P; Roberts, L; Barrett, T
Abstract : Objective: To explore the relationship between frequency of walking trips, perceptions of the local environment and individual travel preferences in children. Design: Cross-sectional questionnaire-based study. Setting: Six primary schools in Birmingham, UK, range of socioeconomic classifications. Participants: 473 children aged 9–11 years (82% response rate), including 250 (52.9%) boys and 160 (33.8%) from ethnic minority populations. Outcome measures: The primary outcome measure was level of walking (high or low) based on self-reported walking frequency in the past week. Secondary outcome measures included child perceptions of seven aspects of the local environment and individual travel preference. All outcomes were measured through questionnaires administered at school in the presence of a researcher. Results: 198 (41.9%) children were classified as high walkers and 275 (58.1%) as low walkers. After adjusting for confounding factors, high walkers were more likely to perceive heavy traffic surrounding their homes (odds ratio (OR) 1.55, 95% confidence interval (CI) 1.03 to 2.33), unsafe streets (OR 1.88, 95% CI 1.27 to 2.80) and prefer healthier modes of travel (OR 1.67, 95% CI 2.56 to 1.08). High walkers were less likely to worry about strangers (OR 0.66, 95% CI 0.45 to 1.02) and less likely to report no parks or sports grounds nearby (OR 0.66, 95% CI 0.42 to 1.02). Children from ethnic minority groups walked significantly less than white children (mean number of walking trips 16.8 and 21.9, respectively, p<0.001). Conclusions: Certain environmental perceptions are related to walking levels in children. Awareness of these may help in the development of future interventions, and also enable healthcare professionals to encourage walking by providing case-specific and appropriate advice.